2021
DOI: 10.1101/2021.11.07.467612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A combinatorial indexing strategy for epigenomic profiling of plant single cells

Abstract: Understanding how cis-regulatory elements facilitate gene expression is a key question in biology. Recent advances in single-cell genomics have led to the discovery of cell-specific chromatin landscapes that underlie transcription programs. However, the high equipment and reagent costs of commercial systems limit their applications for many laboratories. In this study, we profiled the Arabidopsis root single-cell epigenome using a combinatorial index and dual PCR barcode strategy without the need of any specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…A majority of links were within a short distance (<400bp; potential promoter regions), but many links were farther away from genes (potential enhancer regions) (Figures 2B-2C). Cluster marker genes (1,774 genes) had more linked ACRs in a moderately distal region (2.5 kb to 5 kb from TSS) compared with non-marker genes (Figure 2D), implying the role of CREs moderately distal from the TSS in cell type/state-specific gene regulation, which is consistent with the observation in a previous study (Tu et al, 2021). We also found that linked ACRs were slightly larger than non-linked ACRs (Figure S2A).…”
Section: Links Between Gene Expression and Chromatin Accessibilitysupporting
confidence: 91%
“…A majority of links were within a short distance (<400bp; potential promoter regions), but many links were farther away from genes (potential enhancer regions) (Figures 2B-2C). Cluster marker genes (1,774 genes) had more linked ACRs in a moderately distal region (2.5 kb to 5 kb from TSS) compared with non-marker genes (Figure 2D), implying the role of CREs moderately distal from the TSS in cell type/state-specific gene regulation, which is consistent with the observation in a previous study (Tu et al, 2021). We also found that linked ACRs were slightly larger than non-linked ACRs (Figure S2A).…”
Section: Links Between Gene Expression and Chromatin Accessibilitysupporting
confidence: 91%